1996
DOI: 10.1111/j.1365-2672.1996.tb04331.x
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of human colonic bacteria producing phenolic and indolic compounds: effects of pH, carbohydrate availability and retention time on dissimilatory aromatic amino acid metabolism

Abstract: Concentrations of phenolic compounds in human gut contents were more than fourfold higher in the distal colon (6.2 mmol kg-1) compared to the proximal bowel (1.4 mmol kg-1). Tryptophan metabolites were never found in more than trace amounts in large intestinal contents and phenol substituted fatty acids were the major products of aromatic amino acid fermentation that accumulated in the proximal colon, whereas phenol and p-cresol were more important in the distal gut, accounting for 70% of all products of dissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
315
2
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(338 citation statements)
references
References 41 publications
15
315
2
6
Order By: Relevance
“…Even though putrefactive bacteria such as Alistipes and Bacteroides could produce short chain fatty acid from amino acids, carbohydrate fermentation is still preferred 24,39 , which might explain protective roles of fruits and vegetables. In some Fusobacterium species, however, transport of sugar depends on amino acid fermentation (Glu, Lys, His or Ser) 40,41 , suggesting that they only thrive in the presence of an ample supply of amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though putrefactive bacteria such as Alistipes and Bacteroides could produce short chain fatty acid from amino acids, carbohydrate fermentation is still preferred 24,39 , which might explain protective roles of fruits and vegetables. In some Fusobacterium species, however, transport of sugar depends on amino acid fermentation (Glu, Lys, His or Ser) 40,41 , suggesting that they only thrive in the presence of an ample supply of amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The lactic acid produced might help lower the pH and inhibit amino acid degradation in the colon 24,39 . Lactobacillus and Bifidobacterium have been found to stimulate NADPH oxidase 1-dependent ROS generation and intestinal stem cell proliferation 47 , and lactate was reported to accelerate colon epithelial cell turnover in starvation-refed mice 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major source of phenol stems from catabolism of protein and other compounds by gut bacteria, which appears to depend highly on the metabolic activity of the intestinal bacterial microflora. 57,62 A potentially significant source of hydroquinone comes from ingestion of foods containing arbutin, a naturally occurring plant product that is converted to hydroquinone by stomach acids. The wide inter-individual variability in urinary levels of phenol noted above may reflect the wide range of direct intake of phenolic-containing foods and differences among individuals in the composition and chemistry of the gut flora.…”
Section: Dietmentioning
confidence: 99%
“…High background concentrations of phenol, hydroquinone, catechol and 1,2,4-benzenetriol have been measured in the blood, urine and intestines of presumably unexposed humans [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and in the blood and urine of rodents. [63][64][65] Representing measurements of hundreds of individuals in total, these studies showed that mean urinary phenol and hydroquinone levels were about 10 p.p.m.…”
Section: Phenol and Hydroquinone Levels In Unexposed Individualsmentioning
confidence: 99%